Peran Business Intelligence dalam Meningkatkan Efektivitas Operasional dan Kinerja Perusahaan - Achmad Solechan (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study explores the role of Business Intelligence (BI) in improving operational effectiveness and company performance amid rapid digital transformation, big data, Artificial Intelligence (AI), and data analytics development. Using a Narrative Literature Review (NLR) approach, this study analyzed 48 national and international scientific articles related to BI, firm performance, digital transformation, and big data analytics. The findings reveal that BI positively influences decision-making quality, operational efficiency, organizational agility, innovation capability, marketing effectiveness, customer relationship management, and competitive advantage. Furthermore, integrating BI with Big Data Analytics, predictive analytics, machine learning, and AI enhances organizational responsiveness to dynamic business environments. The study also identifies key success factors for BI implementation, including organizational readiness, management support, technological infrastructure, information quality, and system integration. These findings indicate that BI has evolved from a technological tool into a strategic organizational capability that supports sustainable business performance and digital transformation. This study contributes to the Business Intelligence literature by providing a comprehensive understanding of BI’s strategic role across various industries and organizational contexts.